Perspektivy ispol'zovanija DNK-technologij v sporte - Rogozkin, V. A.; Ahmetov, I. I.; Astratenkova, I. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
It becomes evident that the process of physical activity involves a number of polymorphous genes and each of them, taken separately, insignificantly contributes into the overall development of human physical qualities. It is expedient to reveal the associations of individual gene polymorphisms as well as in combination with other poly-morphisms in the process of the obtained data analysis; at the same time it is necessary to consider the impact of combinations of genotypes and alleles with homogeneous effects. In this paper the approaches and the perspectives on the application of DNA technologies in sports are discussed.